Irrational Use of Antibiotics in Medicine: Crisis of Antibiotic Resistance and what We Can Do - Svetlana V. Ilyina (Педиатрическая фармакология, 2018)
Antibiotic overuse in clinical practice not only leads to an increased amount of healthcare costs and a risk of side effects, but also causes an increase of antimicrobial resistance. This is a global problem and an  effective fight bacterial infection depends on its solution. This article  provides a brief overview of the primary situations of irrational antibiotic use among pediatric population and the reasons why doctors  overprescribe antibiotic. The literature based strategies for antibiotics  restrictions are proposed and some generalized rules for a rational antibiotic therapy for physicians and for patients are formulated.